2018
DOI: 10.1038/s41598-018-34205-0
|View full text |Cite
|
Sign up to set email alerts
|

Stable Liposome in Cosmetic Platforms for Transdermal Folic acid delivery for fortification and treatment of micronutrient deficiencies

Abstract: Oral folate fortification has been successful in many developed nations, however, developing countries still face low compliance and high incidence of folate deficiency associated with low birth weight infants and preterm deliveries. We report safe and efficient approach for transdermal systemic folate delivery using fluidising liposomes (120 ± 4 nm) stabilised within 3D matrix of naturally occurring cosmetic bases: Fuller’s earth and henna with room temperature stability. The proof of stratum corneum fluidisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 29 publications
(27 reference statements)
0
24
0
1
Order By: Relevance
“…The technology for transdermal delivery of nutrients using fluidizing phospholipid based liposomes has been developed by Banerjee et al from Nanomedicine laboratory, Department of Biosciences and Bioengineering, IITB, Mumbai, India and has been patented ( 17 ). The technology has demonstrated safety and efficacy in in vitro and in vivo animal models for transdermal delivery of nutrients at supplemental doses ( 18 ). The technology has also demonstrated no irritation potential during irritation patch testing in healthy human volunteers ( 19 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The technology for transdermal delivery of nutrients using fluidizing phospholipid based liposomes has been developed by Banerjee et al from Nanomedicine laboratory, Department of Biosciences and Bioengineering, IITB, Mumbai, India and has been patented ( 17 ). The technology has demonstrated safety and efficacy in in vitro and in vivo animal models for transdermal delivery of nutrients at supplemental doses ( 18 ). The technology has also demonstrated no irritation potential during irritation patch testing in healthy human volunteers ( 19 ).…”
Section: Resultsmentioning
confidence: 99%
“…There is no published literature on transdermal supplementation of folate or vitamin B12 in clinical studies. Our earlier studies have reported the proof of concept preclinical studies for delivery of folate trans-dermally through cosmetics ( 18 ). Thus, this was one of the first attempts to develop and scale up a technology-based intervention for transdermal supplementation of multiple micronutrients through a body oil platform.…”
Section: Discussionmentioning
confidence: 99%
“…They performed ex-vivo experiments using Franz diffusion cells to check the skin permeation. 32 Mithun G. Maniyar et al developed lopinavir encapsulated liposomes for use in anti-HIV therapy. They formed these liposomes using the spray drying method.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…We developed an innovative formulation of body oil containing soya phosphatidylcholine and oleic acid-based liposomes encapsulating iron, folate, vitamin B12, and vitamin D using a patented platform for increased permeation across the stratum corneum barrier (21,22). The liposomes showed high permeation through the stratum corneum and showed 40-50% encapsulation e ciency for ferrous bisglycinate, 20-40% for folate and B12, and 90-95% for vitamin D. The technology has demonstrated safety and e cacy in in-vitro and in-vivo animal models for transdermal delivery of nutrients at supplemental doses (23). The technology was also found to be non-irritant in healthy human volunteers and children (24)(25).…”
Section: Read Full License Introductionmentioning
confidence: 99%